Eco-Nutritional assessment of the knowledge, attitudes and practices of producers, traders and processors in the market gardening sector of greater Lomé - Elom Assinou, Kokou; Kpotchou, Koffi (Edelweiss Applied Science and Technology, 2024)
Societal changes in the food sector are presenting the Greater Lomé Autonomous District (DAGL) with major sustainability challenges. However, the socio-economic, health, nutritional and ecological knowledge, attitudes and practices (KAPs) of stakeholders in solving these problems are only partially taken into account, even in the existing scientific literature. As such, the research aims to assess the level of health, socio-economic and environmental sustainability of market garden vegetable production, trade and processing in the Autonomous District of Greater Lomé (DAGL), based on the principles of nutritional ecology. Using a quantitative multi-criteria approach, 147 people were interviewed : 44 producers, 56 traders and 47 processors. Judgemental sampling was used to form the sample. The data collected by Kobocollect was processed using Excel, Arcgis and Google Earth Pro. Average scores and good KAP rates were calculated for stakeholders according to key aspects of sustainable development apprehension. The results show that in the DAGL, the rates for ecological (26.13%), health (33.71%), socio-economic (42.46), technological and innovative (22.93%) knowledge, attitudes and practices are low. They stand at 30.31%. These results are unfavorable to the achievement of the SDGs, and do not meet the principles of nutritional ecology and standard 13 of the Global Reporting Initiative (GRI) 2023. Hence the importance of designing and implementing an integrated, long-term eco-nutritional education program for all stakeholders.